Evaluation of bacteria and antibiotic resistance profiling of Wara (White soft cheese) in Oyo- State, South West, Nigeria (2017)
Fresh milk from healthy cows contains few bacteria but contamination during handling and processing can rapidly increase bacterial population and subsequently depreciate it quality. This study evaluated thè presence of bacteria and their antibiotic resistance profiles in white soft cheese (Wara) in three major producing locai Government areas in Oyo-State, Nigeria. The cheese samples were collected in sterile universal bottles immediately after production. Samples were immediately transported to thè laboratory for bacteria isolation, identification and antibiotic susceptibility test of thè isolates. A total of one hundred and sixty-five (165) bacterial isolates of ten different bacterial genera were identified from 102 cheese samples. The isolation rates of different species/genera were Lactobacillus spp (39.8%), E. coli (32.5%), Klebsiella spp (9%), Citrobacter spp (2.4%), Acinetobacter spp (3.6%), Pseudomonas spp (6.6%), Bordetella spp (0.6%), Proteus spp (1.2%), Staphylococcus spp (3.6%) and Strepiococcus agalactiae (0.6%). Results demonstrated substantial differences in their resistance pattems to various antibiotics. The isolates were tested against ten different antibiotics. The Gram negative isolates showed twenty-five resistance pattems while Gram positive isolates revealed fifty-four distinct resistance groups. In all, Gram positive isolates showed resistance to ceftriaxone (61.1%), gentamicin (51.4%), chloramphenicol (51.1%), amoxicillin (48.6%), ciprofloxacin (44.4%), cotrimoxazole (43.1%), perfloxacin (40.3%), streptomycin (40.3%) Erythromycin (31.9) and ofloxacin (30.6%) while Gram positive showed resistance to chloramphenicol (22.6%), trimethoprim /sulfamethoxazole (20.4%), amoxillin/clavulanic acid. (10.8%), streptomycin (9.7%), gentamicin (8.6%), sparfloxacin (6.5%), amoxicilin (5.4%), Perfloxacin (5.4%), ofloxacin (4.3%) and ciprofloxacin (3.2%). Multi-drug resistance to three or more antibiotics was observed in 69 isolates, 56 Gram positive and 13 Gram negative bacteria. This study confirmed that white soft cheese “wara” can be a source of bacteria with multidrug resistant phenotypes.